Towards gender equality from service-learning experiences: Teacher perceptions - Cortijo Ruiz, Gemma; Riquelme Soto, Verónica; Galvis Doménech, María José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This research aims to: a) collect and describe those non-university educational experiences carried out between 2017 and 2020 on gender equality collected in the Spanish Service-Learning Network and b) know the perception of professionals as project coordinators. To do this, semi-structured interviews have been carried out (n=7) analyzed through the SWOT matrix. Among the results obtained, the promotion of values of equality and civility stands out, while difficulties such as poor teacher training or low involvement of teachers outside the project are detected.